2010
DOI: 10.1007/s12289-010-0725-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Punch Geometry and Sample Size on the Deep-Drawing Limits in Expansion of an Aluminium Alloy

Abstract: The effects of punch geometry and sample size on forming limit diagrams in expansion are investigated in the case of a 2024 aluminium alloy. Four configurations were selected: flat punch (Marciniak test) or hemispheric punch and decimetric vs. centimetric tooling dimensions. Both decimetric and centimetric deep-drawing devices are associated with an image correlation tool that allows to identify without any contact the deformation on the surface of planar or non-planar specimens. Strains on the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Figure 7 and Figure 8 showed the thickness and stress distributions of the drawn part that occurred in the deep drawing process for Case I with R D = 5 mm, R D1 = 2 mm and R P = 0.8 mm. The numerical results in Figure 7 showed that the drawn part could be punctured on two corners as visible white areas due to too high thinning [ 16 , 17 ]. Especially, the deepest corner of the rectangular shaped pocket (point F) was easy to puncture, and was chosen to be examined in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 and Figure 8 showed the thickness and stress distributions of the drawn part that occurred in the deep drawing process for Case I with R D = 5 mm, R D1 = 2 mm and R P = 0.8 mm. The numerical results in Figure 7 showed that the drawn part could be punctured on two corners as visible white areas due to too high thinning [ 16 , 17 ]. Especially, the deepest corner of the rectangular shaped pocket (point F) was easy to puncture, and was chosen to be examined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…With high peak pressure in the deep drawing process, the failure was at one of the bottom corners where the biaxial stretching was predominant mode of deformation and the thinning in this area was found to be 23–24% at failure. Robert Boissiere et al [ 17 ] examined the effects of punch shapes on the deep drawing limits in expansion. Two punch shapes including the flat punch and the spherical punch were considered with the sheet material of aluminium alloy 2024.…”
Section: Introductionmentioning
confidence: 99%